Etiology-based strabismus classification scheme for pediatricians - Mocan, Mehmet Cem; Pastapur, Aishwarya; Kaufman, Lawrence (The Turkish Journal of Pediatrics, 2022)
Background. Pediatricians are regularly involved in the initial examination of children presenting with strabismus, a common ocular condition occurring in 3% of children. The objective of this review was to gain insight into pediatric residents, fellows and attendings` understanding of strabismus, and to propose an etiology-based strabismus classification scheme to aid this understanding. Methods. A survey was conducted in a single Department of Pediatrics in a university academic institution in order to assess the degree of understanding of the classification, etiology and nomenclature of strabismus. A targeted literature review, pertinent to our classification scheme for strabismus in the pediatric age group, is provided to clarify the various underlying etiological conditions for pediatricians. Results. The surveyed cohort (n=26) consisted of 10 (38.5%) attendings and 16 (61.5%) pediatricians-in-training. Although 69% of survey participants felt comfortable performing an ocular motility evaluation, only 19% had a clear understanding of the underlying etiology of strabismus, 8% had a clear understanding of strabismus nomenclature and none of the participants had clear knowledge of a classification scheme of strabismus. We propose an etiologic-based strabismus classification scheme with streamlined nomenclature geared towards Pediatricians to facilitate the management of pediatric patients with various ocular misalignments. Eight major categories of this classification scheme include (1) physiologic, (2) comitant, (3) paralytic, (4) sensory, (5) syndromic, (6) orbital, (7) supranuclear and (8) pseudostrabismus. Conclusions. Pediatricians at all levels of professional experience have a limited command of strabismus. An etiology-based classification scheme of strabismus may assist in understanding the underlying causes and facilitate the management of strabismus in the pediatrician`s office.
Keywords: pediatric strabismus; strabismus classification; strabismus etiology